PERTANGGUNGJAWABAN PIDANA TERHADAP TINDAK PIDANA MENJEBOL SISTEM PENGAMANAN DATA PRIBADI: STUDI PUTUSAN PENGADILAN NOMOR 809/PID.SUS/2023/PN.MDN - Rahmat Syah Putra Sarumaha, Hendrik; Yunara, Edi; Arifiyanto, Joiverdia (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
"Digital crime" (or "cybercrime") has become one of the most frequently used terms in society today. The prefix "cyber-" is attached to various terms to describe new societal forms or crime types based on cyberspace—such as cyber society, cyberspace, cyberattacks, cybercrime, and cyber-terrorism. The evolution of information technology and the internet has created the realm of cyberspace; this computer-based communication world offers a new reality known as virtual reality. This environment has given rise to the specific term "cybercrime." Some experts argue that computer crime, cybercrime, and telematics crime are essentially the same, differing only in nomenclature. The underlying argument is that while computers were initially used merely for data collection and storage—facilitating conventional crimes—subsequent developments saw crimes committed via the internet, such as Trojan horse attacks and data leakage. This terminological controversy has not sparked significant debate regarding usage; for the sake of consistency, the author employs the term "cybercrime." Advances in information technology—particularly in computing and the internet—have undeniably benefited human life. However, alongside the advantages and conveniences they offer, these technologies possess a dark side capable of destroying human life and culture. Information technology has become a "double-edged sword": while it contributes to human welfare, progress, and civilization, it also serves as an effective vehicle for unlawful acts. Data theft is one such act that can be easily and effectively perpetrated by exploiting technological advancements, particularly in the sectors of data management and the handling of Personal Data—an area requiring robust protection. Advances in information and communication technology have blurred the boundaries of privacy, making it increasingly easy for Personal Data to be disseminated. Information technology can thus be utilized to commit unlawful acts, such as the theft of users' Personal Data.